Bahasa Dakwah Pemerintah Membangun Harmonisasi Kebangsaan - Farhan Farhan (Proceedings of International Conference on Da'wa and Communication, 2019)
This paper examines the reality of Da'wa language in the interaction and communication to the head of state with the peoples. The diversity of tribes, religions, races, and groups within the archipelago needs to be handled wisely, so that the harmonization of citizens continues to be strengthened in all aspects of life. Uploading the message of the head of state on you tube social media can be the right media to parse central and regional policies. You tube social media is a trend of millennial society that is loved by all groups. Therefore, the head of state also needs to upload the existing social media. The message of the head of state needs to be known to all its people, both delivered during state speeches and in remarks on non-state activities. The President is the icon of a country, the national cultural identity of natural resources and human resources must be fully considered. It concerns state policies based on idealized ideals and constitutional grounds. All policies must be understood by the government apparatus from the central to the regions, officials to the people. However, the language of the head of state is not as easy as the educator explains it to students, the head of state needs high social sensitivity, so there is no obstacle means understanding all the messages he conveys. The head of state must provide an optimal and perfect example as a manifesto of the characteristics of Indonesian human resources as a whole. How are the messages of the head of state uploaded on social media ‘You Tube’?. The head of state must provide an optimal and perfect example as a manifesto of the characteristics of Indonesian human resources as a whole. This study is a descriptive qualitative methode, the material from the cyber media, and analysis of the speechs of Ir. Jokowidodo in YouTube media from January to December 2017. The research shows that the president's verbal and non-verbal messages reflected the balance of communication between leaders and the people interactively interactively; the meaning is humanist, religious, humorous, traditionalist, and nationalist. The analysis too shows that the head of the central government until the region must be a communicator, innovator and initiator wholeheartedly dealing with the interests of civil society in the millennial era, guarding the strengthening of national identity and religious ideology.